2014
DOI: 10.1111/idj.12116
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in dental insurance coverage among hospitalised Western Australian children

Abstract: Better understanding of disparities in access to care among children, socioeconomic divide in oral health insurance coverage and subsequent development of intervention programmes, will be critical to improving Australian children's oral health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 5 publications
1
22
0
Order By: Relevance
“…Advances and improvement in oral health have been experienced disproportionately by those with higher socio‐economic status, and there has been increased polarization of dental caries within the community . Dental caries remain one of the leading causes of hospitalization among children in WA …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advances and improvement in oral health have been experienced disproportionately by those with higher socio‐economic status, and there has been increased polarization of dental caries within the community . Dental caries remain one of the leading causes of hospitalization among children in WA …”
Section: Discussionmentioning
confidence: 99%
“…Rates of oral disease are high among these populations and access to treatment is often difficult. Hospitalization for conditions related to oral health are prevalent, and placing considerable burdens on health system budgets . Among preschool children, hospitalization for dental caries was one of the leading causes of hospitalization …”
Section: Introductionmentioning
confidence: 99%
“…A strength of having a widely used statistical index for local area resources in Australia allows for easy investigation of this influence on oral health. Previous research has found, children residing in low SEIFA areas are associated with poorer indicators of oral health (ie, caries) and other risk factors or influences (ie, oral hygiene behaviours and dental service use) . Future studies should consider using more direct measures of social capital such as social capital scales …”
Section: Discussionmentioning
confidence: 99%
“…Previous research has found, children residing in low SEIFA areas are associated with poorer indicators of oral health (ie, caries) and other risk factors or influences (ie, oral hygiene behaviours and dental service use). [42][43][44][45] Future studies should consider using more direct measures of social capital such as social capital scales. 46…”
Section: Community Levelmentioning
confidence: 99%
“…People on lower incomes are less likely to use allied health services (Korda et al 2009). In relation to dental care, research shows inequalities in oral health (Mejia et al 2014), inequities in dental insurance associated with inequities in care (Alsharif et al 2014), and cost as a barrier for lower-income people to access care (Chrisopoulos et al 2013).…”
Section: Other Forms Of Phcmentioning
confidence: 99%